Hollywood vs. the galaxy - Winkler, Henry, 1945-; Oliver, Lin (Winkler, Henry, 1945- Alien superstar (Series) ;, 2021)
After facing off against Citizen Cruel and becoming a fan favorite on his Hollywood sitcom, Buddy Buger has to hide from the Supreme Leader of his home planet and maintain his secret alien identity.